2014
DOI: 10.4103/1742-6413.132997
|View full text |Cite
|
Sign up to set email alerts
|

Is 58% sensitivity for detection of cervical intraepithelial neoplasia 3 and invasive cervical cancer optimal for cervical screening?

Abstract: Recent Food and Drug Administration (FDA) approval of a Roche cobas human papillomavirus (HPV) test application as a first line primary cervical screening tool in women 25 and older introduces a new era of complex cervical screening choices. Perhaps the most surprising findings in Roche's supporting ATHENA trial data were the unexpectedly low verification bias-adjusted CIN3+ sensitivities documented by the FDA for both the proposed cobas HPV testing algorithm (58.26%) and Pap testing algorithm (42.63%). These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…HPV‐only primary screening for cervical cancer presents many challenges for clinicians. Questions arise regarding its effectiveness, its long‐term risk, and when it is the best option for a particular patient . Clinicians had similar questions when cotesting was first recommended for women aged ≥30 years in 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV‐only primary screening for cervical cancer presents many challenges for clinicians. Questions arise regarding its effectiveness, its long‐term risk, and when it is the best option for a particular patient . Clinicians had similar questions when cotesting was first recommended for women aged ≥30 years in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…With more than 250,000 samples, we sought to compare the 3 screening approaches based on cervical biopsy results, including squamous cell carcinoma, adenocarcinoma, and cervical intraepithelial neoplasia (CIN) grade 3 or greater (≥CIN3). Our objective was to provide practical clinical data to inform the discussion regarding the choice of an appropriate cervical cancer screening methodology and to help determine the most effective screening method for the early detection and appropriate treatment of cervical cancer …”
Section: Introductionmentioning
confidence: 99%
“…The introduction of cytology screening (Pap smear) has greatly reduced the mortality and morbidity rates for patients with invasive cervical cancers in the past decades. However, it has been demonstrated that the accuracy of Pap smear test ranged from 20% to 80%, and the results varied substantially in areas with different screening infrastructures, which therefore limited its efficacy for cervical cancer diagnosis (3)(4)(5)(6). Persistently infected by human papillomavirus (HPV) with high risk type remains the major pathogens of cervical cancer, as a result, HPV DNA testing has been adopted for the triage of patients with atypical squamous cells of undetermined significance (2,4,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Primary screening with only HPV testing has been challenged by some authors who have highlighted the improved detection by cotesting and suggested it is insufficiently sensitive alone [19,27,28,29]. Amidst the controversy, the characteristics of HPV screening test-negative cases with cytology positive for dysplasia remain ill-defined.…”
Section: Introductionmentioning
confidence: 99%